Effects of Agricultural Productivity Shocks on Female Labor Supply: Evidence from the Boll Weevil Plague in the US South - Philipp Ager; Markus Bruckner; Benedikt Herz (European Historical Economics Society (EHES), 2014)
In the beginning of the 1890s, counties located in the Cotton Belt of the American South were hit by an agricultural plague, the boll weevil, that adversely affected cotton production and hence the demand for labor. We use variation in the incidence of the boll weevil multiplied with counties' initial cotton share to construct instrumental variables estimates of the labor supply curve. Controlling for county and state-by-time fixed effects, we find a significant positive response of labor supply to changes in labor income. The effect is particularly large for females, consistent with evidence that females had a comparative advantage in picking cotton.
Keywords: 330; Labor Supply; Female Labor Force Participation; Agricultural Productivity Shocks; US South; Boll Weevil